Symmetrical and Asymmetrical Multilevel Inverter Structures with Reduced Number of Switching Devices - M. H. Yatim; A. Ponniran; M. A. Zaini; M. S. Shaili; N. A. S. Ngamidun; A.N. Kasiran; A. A. Bakar; J.N. Jumadril (Institute of Advanced Engineering and Science, 2018)
The purpose of this study is to analyze the operation and design of symmetrical and asymmetrical multilevel inverter structures with reduced number of switching devices. In this study, the term of conventional inverter is defined as a single cascaded inverter. Specifically, the inverter operates in three complete loops and only produces 2-level and 3-level of output voltages. Usually, cascaded structure suffers from the high total harmonic distortion. Thus, by considering multilevel structure of inverter, low total harmonic distortion reduction and voltage stress reduction on switching devices can be archived. Sinusoidal pulse width modulation and modified square pulse width modulation are used as modulation techniques in switching schemes of the designed multilevel inverters. The findings indicate that, the designed multilevel structure cause low total harmonics distortion at the output voltage. Furthermore, the asymmetrical structure is producing the same output voltage levels with reduced number of switching devices compared to the symmetrical structure is experimentally confirmed. The findings show that the total harmonic distortion for 7-level (symmetrical) and 9-level (asymmetrical) are 16.45% and 15.22%, respectively.